2012
DOI: 10.1021/jf301600m
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production and Characterization of the Sweet-Tasting Brazzein Secreted by the Yeast Pichia pastoris

Abstract: Brazzein is a small, heat-, and pH-stable sweet protein present in the fruits of the West African plant Pentadiplandra brazzeana Baillon. It exists in two forms differing in sweetness intensity. The major form, called pyrE-bra, contains a pyroglutamic acid at its N-terminus, while the minor form, called des-pyrE-bra, lacks this residue. Here we describe the heterologous expression in the methylotrophic yeast Pichia pastoris of two natural forms of brazzein, pyrE-bra and des-pyrE-bra, and an additional form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
4
24
0
2
Order By: Relevance
“…The estimated threshold values of sucrose and brazzein obtained with the SIAM yes‐no task were approximately 3.2 mg/ml and 4.4 × 10 −3 mg/ml, respectively. These values were significantly different from those reported by Assadi‐Porter et al (), but similar to those reported by Poirier et al (). Other studies using a variety of methods estimated the threshold of sucrose to be 2.7–4.3 mg/mL, which is 2.3‐ to 3.7‐fold lower than the value estimated by Assadi‐Porter et al (), Fukunaga, Uematsu, and Sugimoto (), James, Laing, and Oram (), Kunka, Doty, and Settle (), and Shepherd, Quek, and Pathirana ().…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…The estimated threshold values of sucrose and brazzein obtained with the SIAM yes‐no task were approximately 3.2 mg/ml and 4.4 × 10 −3 mg/ml, respectively. These values were significantly different from those reported by Assadi‐Porter et al (), but similar to those reported by Poirier et al (). Other studies using a variety of methods estimated the threshold of sucrose to be 2.7–4.3 mg/mL, which is 2.3‐ to 3.7‐fold lower than the value estimated by Assadi‐Porter et al (), Fukunaga, Uematsu, and Sugimoto (), James, Laing, and Oram (), Kunka, Doty, and Settle (), and Shepherd, Quek, and Pathirana ().…”
Section: Resultssupporting
confidence: 49%
“…Other studies using a variety of methods estimated the threshold of sucrose to be 2.7–4.3 mg/mL, which is 2.3‐ to 3.7‐fold lower than the value estimated by Assadi‐Porter et al (), Fukunaga, Uematsu, and Sugimoto (), James, Laing, and Oram (), Kunka, Doty, and Settle (), and Shepherd, Quek, and Pathirana (). Poirier et al () suggested that these differences in threshold were related to differences in the methods used to estimate the thresholds. Therefore, the sweetness potency (or ratio) between the control substance sucrose and brazzein should be analyzed for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeasts Saccharomyces cerevisiae, Pichia pastoris, Hansulae polymopha, and Kluyveromyces lactis have been widely used as a host to produce heterologous proteins [11][12][13]. These yeast expression systems have advantages that include eukaryotic quality-control machinery, fast growth rate, high cell density, facile genetic manipulation, and inexpensive growth medium.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recombinant proteins produced in yeast have been expressed by S. cerevisiae strains [11,12]. Recently, Poirier et al [13] reported the heterologous expression in the yeast P. pastoris of two natural forms of brazzein, and a mutant called Q1-bra. Recombinant proteins were induced by adding 1% methanol twice a day for 6 days, and approximately 30-90 mg/L was obtained.…”
Section: Introductionmentioning
confidence: 99%